2013
DOI: 10.1115/1.4023611
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Low Pressure Steam Turbine Exhaust Hood and Diffuser Studies

Abstract: This paper summarizes the findings from research studies carried out over the last 30 years, to better understand the flows in steam turbine low pressure exhaust hoods and diffusers. The work aims to highlight the areas where further study is still required. A detailed description of the flow structure is outlined and the influence of the last turbine stage and the hood geometry on loss coefficient is explored. At present, the key challenge faced is numerically modeling the three-dimensional, unsteady, transon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The total KE flux was also considered, differing from Eq. (2) in that it incorporates all three velocity components for the KE nonuniformity (Ux, Uy, Uz)…”
Section: Journal Of Engineering For Gas Turbines and Powermentioning
confidence: 99%
See 1 more Smart Citation
“…The total KE flux was also considered, differing from Eq. (2) in that it incorporates all three velocity components for the KE nonuniformity (Ux, Uy, Uz)…”
Section: Journal Of Engineering For Gas Turbines and Powermentioning
confidence: 99%
“…Burton et al [2] summarized the most recent studies of steam turbine exhaust hood and diffuser performance. Owczarek et al [3], Zhang et al [4], and Yoon et al [5] found that the major sepa ration region appears behind the diffuser casing or the flow guide.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates the use of lowfidelity numerical models to reduce the computational demand to levels suitable for use in industrial design processes over the last two decades. A summary of these methods which couple the turbine last stage and the exhaust hood has been discussed by Burton et al (2013). The simulation of isolated exhaust hood from the last stage blade could drastically reduce the computational power.…”
Section: Introductionmentioning
confidence: 99%
“…For recent years, researches on the aerodynamic performance of exhaust passage focus principally on the structure redesign in such aspects as the flow guide, guiding cone, and built-in guide device (Fan et al 2007 andBurton et al 2013). Among the common methods of providing flow characteristics in the exhaust passage are a full-scale model test (Lagun et al 1984), scale-model experiment (Zhang et al 2007 andVeerabathraswam et al 2016), and numerical investigation (Yoon et al 2002 andMizumi et al 2013).…”
Section: Introductionmentioning
confidence: 99%